The value of dynamic magnetic resonance imaging in interdisciplinary treatment of pelvic floor dysfunction - Attenberger, Ulrike; Budjan, Johannes; Herold, Alexander; Kienle, Peter; Kleine, Werner; Häcker, Axel; Heinzelbecker, Julia; Schönberg, Stefan; Michaely, Henrik J. M. (Abdominal imaging, 2015)
PurposeThe purpose of this study was to determine the value of dynamic pelvic floor MRI relative to standard clinical examinations in treatment decisions made by an interdisciplinary team of specialists in a center for pelvic floor dysfunction.Methods60 women were referred for dynamic pelvic floor MRI by an interdisciplinary team of specialists of a pelvic floor center. All patients were clinically examined by an urologist, gynecologist, a proctological, and colorectal surgeon. The specialists assessed individually and in consensus, whether (1) MRI provides important additional information not evident by physical examination and in consensus whether (2) MRI influenced the treatment strategy and/or (3) changed management or the surgical procedure.ResultsMRI was rated essential to the treatment decision in 22/50 cases, leading to a treatment change in 13 cases. In 12 cases, an enterocele was diagnosed by MRI but was not detected on physical exam. In 4 cases an enterocele and in 2 cases a rectocele were suspected clinically but not confirmed by MRI. In 4 cases, MRI proved critical in assessment of rectocele size. Vaginal intussusception detected on MRI was likewise missed by gynecologic exam in 1 case.ConclusionMRI allows diagnosis of clinically occult enteroceles, by comprehensively evaluating the interaction between the pelvic floor and viscera. In nearly half of cases, MRI changed management or the surgical approach relative to the clinical evaluation of an interdisciplinary team. Thus, dynamic pelvic floor MRI represents an essential component of the evaluation for pelvic floor disorders.
Gesehen am 25.01.2018